Structure of native photosystem II assembly intermediate from Chlamydomonas reinhardtii - Fadeeva, Mariia; Klaiman, Daniel; Kandiah, Eaazhisai; Nelson, Nathan (Frontiers in Plant Science, 2024)
Chlamydomonas reinhardtii Photosystem II (PSII) is a dimer consisting of at least 13 nuclear-encoded and four chloroplast-encoded protein subunits that collectively function as a sunlight-driven oxidoreductase. In this study, we present the inaugural structure of a green alga PSII assembly intermediate (pre-PSII-int). This intermediate was isolated from chloroplast membranes of the temperature-sensitive mutant TSP4, cultivated for 14 hours at a non-permissive temperature. The assembly state comprises a monomer containing subunits A, B, C, D, E, F, H, I, K, and two novel assembly factors, Psb1 and Psb2. Psb1 is identified as a novel transmembrane helix located adjacent to PsbE and PsbF (cytochrome b559). The absence of PsbJ, typically found in mature PSII close to this position, indicates that Psb1 functions as an assembly factor. Psb2 is an eukaryotic homolog of the cyanobacterial assembly factor Psb27. The presence of iron, coupled with the absence of QA, QB, and the manganese cluster, implies a protective mechanism against photodamage and provides insights into the intricate assembly process.